Meta-regression analysis: Producing credible estimates from diverse evidence - Chris Doucouliagos (IZA World of Labor, 2016)
Good policy requires reliable scientific knowledge, but there are many obstacles. Most econometric estimates lack adequate statistical power; some estimates cannot be replicated; publication selection bias (the selective reporting of results) is common; and there is wide variation in the evidence base on most policy issues. Meta-regression analysis offers a way to increase statistical power, correct the evidence base for a range of biases, and make sense of the unceasing flow of contradictory econometric estimates. It enables policymakers to develop evidence-based policies even when the initial evidence base lacks credibility.
Keywords: C01; C50; 330; bias; credibility; research synthesis; meta-regression